IMF Staff papers : Volume 23 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1976)
This paper examines the proposition that flexible exchange rates are more (less) inflationary than a system of fixed exchange rates. The paper first discusses possible effects of a change in the exchange rate regime on the price level. It examines the two arguments that flexible exchange rates will increase world prices both by increasing costs of production and by reducing either the official or private demand for money. The effects of the exchange rate regime on the continuing rate of inflation are discussed next and are divided into those that affect a government's policy preferences in the demand-management area and those that affect the perceived short-term trade-off between inflation and unemployment. the paper concludes that despite the numerous arguments and counterarguments and despite the importance attached to this issue in discussions of international monetary reform, the type of exchange rate system is likely to have little influence on the average rate of world inflation.